1991
DOI: 10.1002/jobm.3620310510
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cytochrome P‐450 in Cunninghamella elegans intact protoplasts and cell‐free preparations capable of steroid hydroxylation

Abstract: Cytochrome P-450 was shown to be involved in 11 alpha-, and 11 beta-hydroxylation of Substance S in intact C. elegans protoplasts. The steroid transformation was inhibited by carbon monoxide, the inhibitory effect being dependent on CO concentration. The function of cyt P-450 in intact protoplasts was confirmed by the estimation of strong absorption at 450 nm in the CO difference spectrum. The presence of antimycin A was necessary to prevent the reduction of the cytochrome oxidase and its interference with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…C. elegans IM 1785/21Gp possesses cytochrome P-450 monooxygenase responsible for corticosteroid 11-hydroxylation (oxygen introduction into cortexolone). This enzyme is always present in the cells on the low level and is rapidly synthesised in the presence of exogenous steroid substrate (DŁUGOŃSKI et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans IM 1785/21Gp possesses cytochrome P-450 monooxygenase responsible for corticosteroid 11-hydroxylation (oxygen introduction into cortexolone). This enzyme is always present in the cells on the low level and is rapidly synthesised in the presence of exogenous steroid substrate (DŁUGOŃSKI et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The xenobiotic steroid hydroxylases are distinct from demethylases of membrane biogenesis and from the biosynthetic steroid monooxygenases (SMITH et al 1994). It was shown that Cunninghamella elegans cytochrome P-450 is involved in 11αand 11β-hydroxylation of cortexolone (DŁUGOŃSKI et al 1991). Microbial 11-hydroxylation of cortexolone belongs to the most important steroid transformations and is used for manufacturing of cortisol and other medical steroids (SEDLACZEK 1988, SCHMAUDER et al 1991, MAHATO and GARAI 1997.…”
mentioning
confidence: 99%
“…The actual involvement of cytochrome P450 enzymes in the site-specific hydroxylation of progesterone has been shown in a number of fungi, like C. elegans (Dlugonski et al, 1991), Aspergillus fumigatus (Smith et al, 1994), Paecilomyces lilacinus (Vitas et al, 1995), and Rhizopus nigricans (Breskvar et al, 1991;Breskvar and HudnikPlevnik, 1977). By protein purification of the progesterone hydroxylation enzyme system from P. blakesleeanus and subsequent reconstitution studies, Ahmed et al (1995) clearly proved the involvement of a cytochrome P450 system in this bioconversion.…”
Section: Bioconversion Of Steroid Moleculesmentioning
confidence: 96%
“…are commonly used reactions in the steroid industry. It has been reported for several species of filamentous fungi including Phycomyces bakesleeanus, Cochliobolus lunatus, Cunninghamella elegans, Aspergillus fumigatus, A. ochraceus, Rhizopus nigricans, and Penicillium raistrickii that the hydroxylations of the steroid skeleton structure are catalyzed by a family of enzymes, the cytochromes P450 (CYPs) (Ahmed et al, 1995;Breskvar and Hudnik-Plevnik, 1981;Dlugonski et al, 1991;Irrgang et al, 1997;Samanta and Ghosh, 1987;Smith et al, 1994).…”
Section: Introductionmentioning
confidence: 99%